Discussion Activities on Educational Problems at the Border of Nusa Tenggara Timur with Nusa Cendana University Students - Posma Sariguna Johnson Kennedy; Suzanna Josephine L.Tobing; Rutman L. Toruan; Anton Nomleni; Santi Lina (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
This activity aims to deepen educational problems in Nusa Tenggara Timur Province (NTT) border between Indonesia and Timor Leste. The implementation of this activity is to conduct discussions to increase understanding of strategic issues regarding educational problems with lecturers and postgraduate students at Nusa Cendana University, Kupang NTT. The method of writing this paper is to use a qualitative approach by reviewing various kinds of literature and discussions carried out. The growth of education services in NTT is increasing in line with educational investments made by the government, such as increasing the number of classrooms in high schools, vocational schools, and universities/polytechnics. However, the average education rating in NTT is still the fourth lowest in Indonesia. The district with the worst conditions on the border is Malacca. The areas that need attention as the next priority are the districts of Kupang and Belu, which the State of Timor Leste borders.